2021
DOI: 10.1039/d0se01160f
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the theoretical window to fabricate high performance inorganic perovskite solar cells

Abstract: Perovskite solar cells (PSCs) have celebrated a decade of intense investigation as a promising photovoltaic technology, measuring a power conversion efficiency of >25.2% with the use of lead based light...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Because of its formation, the propagation of holes to the back contact will be hindered, causing the reduction of the PCE of the PSC. 5…”
Section: Effect Of the Change In Electron Affinity Of Htlmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its formation, the propagation of holes to the back contact will be hindered, causing the reduction of the PCE of the PSC. 5…”
Section: Effect Of the Change In Electron Affinity Of Htlmentioning
confidence: 99%
“…4 These ions are extremely volatile and hygroscopic, thus making the device unstable and more intolerant of heat and moisture. 5 Ti-based A 2 +1 Ti +4 X 6 À1 double perovskites are leadfree and nontoxic materials that not only can substitute the lead in perovskite but also possess novel optoelectronic applications besides solar cells. 6 According to the density functional theory (DFT) calculations, these HPs have advantageous electronic and optical properties, such as appropriate bandgaps and tuneable defect properties.…”
Section: Introductionmentioning
confidence: 99%
“…The VBO is a parameter to measure the energy level between the perovskite layer and HTL. We have demonstrated that reducing the VBO will help to improve the Voc in PSCs 39 . Thus, we have employed PTAA (-5.25 eV) as an HTL, it has a deep energy level compared to the perovskite layer (-5.4 eV) in contrast with Spiro-OMeTAD (-5.11 eV) as shown (Fig.…”
Section: Alternative Etls and Htlsmentioning
confidence: 93%
“…The energy level aligning between the interlayers as well as the stability of selective layers in the PSCs architect is a key to minimize the energy loss. 37,39 Using CeOx as an ETL can be an effective path to improve the performance in lead-free PSCs. Firstly (Fig.…”
Section: Alternative Etls and Htlsmentioning
confidence: 99%
See 1 more Smart Citation